(untitled) (Scientific journal of the Fergana State University, 2023)
New Uzbekistan is creating all opportunities to strengthen the health of young people. For them to develop their bodies, doctors are always ready in all stadiums and sports fields and open sports dispensaries for them to practice properly. Physically cultured means that they have enough physical and mental capabilities to endure any situation.There are more than 100 tests to check the health of young people. These tests comprehensively check and evaluate a person’s health. Of course, the physical development of a person depends on the signs of his body morphology and functional condition. These traits determine its strength and endurance, and these traits are innate (genotype). But its living conditions and upbringing (phenotype) can adapt the genotype to life. We can measure this adaptation process. But in recent years, we realized that the cardiovascular system is more important among these tests, and in this article we tried to evaluate the health of a person through the cardiovascular system (1,2,3,4).